Properties of κ‐Ga2O3 Prepared by Epitaxial Lateral Overgrowth - Alexander Polyakov; In‐Hwan Lee; Vladimir Nikolaev; Aleksei Pechnikov; Andrew Miakonkikh; Mikhail Scheglov; Eugene Yakimov; Andrei Chikiryaka; Anton Vasilev; Anastasia Kochkova; Ivan Shchemerov; Alexey Chernykh; et al. (Advanced Materials Interfaces)
Abstract The structural and electrical properties of undoped and Sn doped κ‐Ga2O3 layers grown by epitaxial lateral overgrowth on TiO2/sapphire substrates using stripe and point masks show that the crystalline structure of the films can be greatly improved relative to conventional planar growth. The undoped films are semi‐insulating, with the Fermi level pinned near EC‐0.7 eV, and deep electron traps at EC‐0.5 eV and EC‐0.3 eV are detectable in thermally stimulated current and photoinduced current transient spectra measurements. Low concentration Sn doping results in net donor concentrations of ≈ 1013 cm−3, and deep trap spectra determined by electron traps at EC‐0.5 eV, and deep acceptors with an optical ionization threshold near 2 and 3.1 eV. Treatment of the samples in hydrogen plasma at 330 °C increases the donor density near the surface to ≈ 1019 cm−3. Such samples show strong persistent photocapacitance and photoconductivity, indicating the possible DX‐like character of the centers involved. For thin (5 µm) κ‐Ga2O3 films grown on GaN/sapphire templates, p‐type‐like behavior is unexpectedly observed in electrical properties and  we  discuss the possible formation of a 2D hole gas at the κ‐Ga2O3/GaN interface.